“It’s my life, it’s my choice and I want to say when” vs “A good death is to be on good terms with God”. Comparing the views of people with dementia in the UK and Brazil about a good death: a cross-cultural qualitative study - Mikelyte, Rasa; Dening, Karen Harrison; Oliveira, Déborah; Vanelli, Julia Maria [UNESP]; Neves, Adriele Ferreira [UNESP]; Dekker, Natashe Lemos; Roque, Francelise Pivetta; Vidal, Edison Iglesias de Oliveira (Springer Nature, 2025)
BackgroundIt is unclear what People Living with Dementia (PLwD) consider a good death to entail, or how those perspectives vary according to culture and context. We aimed to compare the meaning of a good death for PLwD in Brazil and in the United Kingdom (UK).MethodsIn this cross-sectional qualitative study, we conducted semi-structured interviews with a convenience sample of 32 PLwD (16 in Brazil and 16 in the UK) using jointly designed, equivalent interview guides. Two teams of interdisciplinary researchers independently analysed transcripts for their country using inductive thematic analysis, followed by jointly developing overarching themes on the contrasts and similarities across both settings.ResultsWe identified three shared themes: choice and control; spirituality; and fears and wishes. Choice and control permeated all aspects of what a good death meant to PLwD in the UK but was largely absent from Brazilian narratives. The opposite was true for spirituality, which was central to the meaning of a good death in Brazil, while far less prominent in the UK. In both countries, previous experiences with the death of others often shaped wishes and fears towards their own deaths.ConclusionOur results have potential to expand the awareness and sensitivity of health and social care professionals around different cultural views on what a good death means for PLwD and what helps or hinders achieving it. Additionally, our findings challenge global indices of quality of death that do not take cultural and contextual differences into account.